The hormonal correlates of implicit power motivation - Stanton, Steven J. (2009)
Attempts to link testosterone to dominance dispositions using self-report measures of dominance have yielded inconsistent findings. Similarly, attempts to link testosterone changes to a situational outcome like winning or losing a dominance contest have yielded inconsistent findings. However, research has consistently shown that an indirect measure of an individual’s dominance disposition, implicit power motivation, is positively related to baseline testosterone levels and, in interaction with situational outcomes, predicts testosterone changes. We propose a hormonal model of implicit power motivation that describes how testosterone levels change as an interactive function of individuals’ implicit power motivation and dominance situations. We also propose that estradiol, and not testosterone, plays a key role in dominance motivation in women.